Energy level structure of the ground configuration in the Er3+ free ion. (May 2015) - Radžiūtė, L; Kato, D; Gaigalas, G; Jönsson, P; Rynkun, P; Jonauskas, V; Kučas, S
Abstract Energy levels of the ground configuration [Xe]4f11 in the Er3+ ion are reported from relativistic configuration interaction calculations. Calculations are performed using the relativistic atomic structure package GRASP2K, which implements the multiconfiguration Dirac–Hartree–Fock method. The Breit transverse interaction and leading QED effects are included as perturbations. The final energies of 41 levels are compared with results from experiment and semi-empirical methods.